Traditional Chinese marriage after the enactment of the marriage law in Indonesia (Study on the Chinese community of Cirebon City) - Cynthia Monica Az Zahro; Indah Gita Syamsiatin; Rd. Dita Puspita Nadjib; Dudung Hidayat; Diky Dikrurahman (International Journal Labs, 2024)
Indonesia is a multi-ethnic country with a diversity of tribes and cultures that are still preserved and implemented, one of which is the Chinese ethnic culture. There have been cross-country and different religious marriages that were not previously registered in the Civil Registry and then registered, but there are still many misconducts due to ignorance and lack of socialization by the more intensive government, which has resulted in children born to become illegitimate children. The actual circumstances make it difficult for a portion of the ethnic Chinese majority to obtain the legality of their birth certificates, which will affect their future lives. This research method uses empirical jurisprudence with a qualitative approach, so it aims to provide a deeper insight into changes and adaptations in Chinese ethnic marriage institutions after the implementation of national marriage law regulation. Thus, the settlement measure taken after the entry into force of Law No. 1 of 1974 on Marriage in a customaryly married couple, giving birth to an out-of-marriage child by an act on behalf of the mother, which if it is to be authenticated as the child of the father and mother, requires a court decision.